Evaluation of credit assessment & risk grading management of Dutch Bangla Bank ltd. - Anwar, Ashfaq Mustafa (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.